Macrogeographic variation of a pond predator's top‐down effects in a common garden environment. Issue 1 (2nd November 2020) - Stemp, Kenzi M.; Anderson, Thomas L.; Davenport, Jon M.
Abstract: Geographic variation in species behavior and life history has been well documented in biology. Species with wide geographic distributions (i.e., across a continent) but small home ranges (i.e., <1 km 2 ) likely experience wide variability in abiotic environments across the entirety of their range, possibly exhibiting strong local adaptation. Understanding variation across a large geographic scale is especially important when considering species that have strong ecological importance, such as keystone species. Yet, few studies have compared the potential cascading ecological effects of a predator with a keystone role in at least part of its range. To understand how keystone ability in pond food webs can vary across a large geographic range, we conducted an artificial pond experiment with a known keystone predator in at least part of its range, the marbled salamander ( Ambystoma opacum ). To do so, we collected size‐matched salamander larvae from three geographically distant populations (>650 km apart) in Ohio, Mississippi, and North Carolina and placed them in mesocosms with a suite of spring breeding amphibian prey species. We observed differential survival of some prey species leading to differences in spring‐breeding amphibian diversity among the three predator populations, indicating that keystone predation may vary at a geographic scale. Prey diversity was lowest with predators from northern (Ohio) populations of salamanders. Further understanding of large‐scale variability in ecologically important predators and the potential effects of translocating wide‐ranging ambystomatid species is needed to direct future conservation efforts and preserve biodiversity. Abstract : Keystone ability and ecological function can vary across the distribution of a large‐ranging predator. We used predatory salamander larvae (a known keystone) and a suite of amphibian prey to conduct a size‐matched common garden experiment with three populations of predators. Community diversity varied significantly between predator populations, with some impacts cascading to lower trophic levels.